Human impact on long‐term organic carbon export to rivers. Issue 4 (28th April 2017) - Noacco, Valentina; Wagener, Thorsten; Worrall, Fred; Burt, Tim P.; Howden, Nicholas J. K.
Abstract: Anthropogenic landscape alterations have increased global carbon transported by rivers to oceans since preindustrial times. Few suitable observational data sets exist to distinguish different drivers of carbon increase, given that alterations only reveal their impact on fluvial dissolved organic carbon (DOC) over long time periods. We use the world's longest record of DOC concentrations (130 years) to identify key drivers of DOC change in the Thames basin (UK). We show that 90% of the long‐term rise in fluvial DOC is explained by increased urbanization, which released to the river 671 kt C over the entire period. This source of carbon is linked to rising population, due to increased sewage effluent. Soil disturbance from land use change explained shorter‐term fluvial responses. The largest land use disturbance was during the Second World War, when almost half the grassland area in the catchment was converted into arable land, which released 45 kt C from soils to the river. Carbon that had built up in soils over decades was released to the river in only a few years. Our work suggests that widespread population growth may have a greater influence on fluvial DOC trends than previously thought. Key Points: World's longest fluvial DOC concentration record supports models to link monotonic DOC increase since 1880 Population rise caused long‐term increase in fluvial DOC in the Thames basin due to greater sewage effluent loading to the river Short‐term land use change reversed decades of cumulative carbon storage in soils and caused short‐term DOC variability but no overall trend